Printmaking Today: Printmaking in the Midst of Rapid Imaging - Herawan, Michael Binuko Sri; Durahman, Deden Hendan (Journal of Posthumanism, 2025)
The debate and tug-of-war between conventional printmaking and non-conventional printmaking in Indonesia indicates that this branch of art is adapting to change. Printmaking conventions emphasise the quality and skill (printmaking proper) of techniques, as well as the necessary conditions to be worthy of the label "printmaking," before focusing on content. Meanwhile, expanded or expansive printmaking seeks to break the boundaries of convention and explores new opportunities. Both conventional and expanded/expansive printmaking are essential. Printmaking conventions play a vital role in educating the public and novice collectors about the fundamental aspects of craftsmanship and beauty. Additionally, editions—which are part of conventions—make printmaking more affordable. On the other hand, expanded or expansive printmaking is necessary to adapt and accommodate the latest technological developments, producing a variety of new hybrid possibilities and opening up opportunities for ideas and discourse that are crucial in attracting the attention of the mainstream contemporary art scene. This research attempts to further understand printmaking as a medium, not only through images but also through the processes, materials, and stages involved in it. Meaning in a medium can be deeply personal and arbitrary, but it cannot serve as a conceptual basis. When viewed as a medium, the various techniques in printmaking transcend mere techniques.